Vergilius, Horatius és Ovidius magyarországi recepciója Palingenius Zodiacus vitae-jének magyar fordításaiban - Knapp, Éva (Antikvitás & Reneszánsz, 2019)
The Italian humanist Marcellus Palingenius Stellatus, the author of Zodiacus vitae, a popular teaching poem (philosophical poem, epic, “great epic”) published in several editions and translations throughout Europe for centuries, is one of the mysterious figures in the history of European literature. His biography is largely uncertain, and is mainly derived from the work itself. this work is a moral and philosophical poem divided into twelve books according to the signs of the zodiac. The zodiac signs follow each other according to the ancient Roman calendar. To summarize the knowledge of man available in the early 16th century, Palingenius used the works of antique authors, especially the poems of Virgil, Horace and Ovid. His allusions, adaptations and transpositions, as well as their sources, are extremely diverse. After the first Venetian edition presumably dated 1531, new editions of the book appeared in succession, even though it was constantly on the list of forbidden books (Index librorum prohibitorum) from 1557 onwards. The impact history of the work has long been a separate research topic, but it has not been dealt with in Hungary so far. Translations of the national languages of the Zodiacus vitae have been and continue to be produced since the second half of the 16th century. The first and still the only complete manuscript translation in Hungarian was made by József Elefánti Jáklin in 1771. The manuscript was not published, but several copies survived in Bratislava, Budapest, Eger and Pécs. There is no exact answer to the question of which Latin edition Jáklin translated as the catalogue of the his library is unknown.